2022
DOI: 10.1136/bmjdrc-2022-002806
|View full text |Cite
|
Sign up to set email alerts
|

Making an impact on kidney disease in people with type 2 diabetes: the importance of screening for albuminuria

Abstract: Albuminuria is useful for early screening and diagnosis of kidney impairment, especially in people with pre-diabetes or type 2 diabetes (T2D), which is the leading cause of chronic kidney disease (CKD) and end-stage kidney disease (ESKD), associated with increased mortality, poor cardiovascular outcomes, and high economic burden. Identifying patients with CKD who are most likely to progress to ESKD permits timely implementation of appropriate interventions. The early stages of CKD are asymptomatic, which means… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 60 publications
(67 reference statements)
0
10
0
Order By: Relevance
“…In 2015, it was reported that 415 million people aged 20-79 have diabetes, which is expected to reach 642 million by 2040 [ 3 , 4 ]. Globally, the number of diabetes patients has quadrupled in the past few years, and 90% of diabetes patients are type 2 diabetes [ 5 ], which is mainly caused by insulin resistance due to various reasons [ 6 ]. Due to the change of dietary structure and the reduction of physical activity, obese children are gradually increasing, and the number of children and adolescents with type 2 diabetes is raising year after year [ 7 ], although type 1 diabetes is mostly in children.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, it was reported that 415 million people aged 20-79 have diabetes, which is expected to reach 642 million by 2040 [ 3 , 4 ]. Globally, the number of diabetes patients has quadrupled in the past few years, and 90% of diabetes patients are type 2 diabetes [ 5 ], which is mainly caused by insulin resistance due to various reasons [ 6 ]. Due to the change of dietary structure and the reduction of physical activity, obese children are gradually increasing, and the number of children and adolescents with type 2 diabetes is raising year after year [ 7 ], although type 1 diabetes is mostly in children.…”
Section: Introductionmentioning
confidence: 99%
“…The causes of T2D include obesity, physical inactivity, and genetic factors [79][80][81]. If left untreated, T2D can cause other health problems, including CVD [82], high blood pressure (hypertension) [83], vision loss (diabetic retinopathy) [84], and kidney disease [85]. Thus, intensive T2D research is ongoing to understand the impact of T2D to other health problems, including CMD.…”
Section: Diabetes-associated Lncrnasmentioning
confidence: 99%
“…American Diabetes Association (ADA) and KDIGO have adopted a scheme incorporating both eGFR and UACR for CKD risk assessment in patients with T2DM 5 . Quantification of albuminuria with UACR is considered a powerful screening tool for the prompt identification of kidney damage in early, asymptomatic stages of diabetic kidney disease 6 . Of importance, it seems that albuminuria, as a marker of kidney damage in the context of T2DM, progresses irrespective of eGFR levels, emphasizing the absolute need for the meticulous, periodic evaluation of both parameters in clinical practice 7 .…”
Section: Introductionmentioning
confidence: 99%
“…5 Quantification of albuminuria with UACR is considered a powerful screening tool for the prompt identification of kidney damage in early, asymptomatic stages of diabetic kidney disease. 6 Of importance, it seems that albuminuria, as a marker of kidney damage in the context of T2DM, progresses irrespective of eGFR levels, emphasizing the absolute need for the meticulous, periodic evaluation of both parameters in clinical practice. 7 Besides its importance in the development and progression of CKD, albuminuria also appears to be a significant prognostic marker of all-cause mortality, cardiovascular morbidity and mortality, irrespective of the presence of baseline T2DM.…”
mentioning
confidence: 99%